Localized Lymph Node Light Chain Amyloidosis. (2nd April 2015) - Dhakal, Binod; Harrington, Alexandra M.; Stadler, Michael E.; D'Souza, Anita
Abstract : Immunoglobulin-derived light chain amyloidosis can occasionally be associated with localized disease. We present a patient with localized lymph node light chain amyloidosis without an underlying monoclonal protein or lymphoproliferative disorder and review the literature of lymph node amyloidosis discussing work-up and risk factors for systemic progression.